A Novel Electrostatic Actuator Class. (2016) - Conrad, H.; Kaiser, B.; Gaudet, M.; Langa, S.; Stolz, M.; Uhlig, S.; Schimmanz, K.; Schenk, H.
Abstract: Common quasi-static electrostatic micro actuators have significant limitations in deflection due to electrode separation and unstable drive regions. These actuators suffer from an operational instability, the so-called pull-in effect that limits the actuators' travel range to one third of the electrode separation. High driving voltages and large electrode gaps are required to achieve large displacements. In our work, we present a novel electrostatic actuator class, which allows high deflections with nanometric electrode separation. The approach presented utilizes a bimorph like effective lever to transform electrostatic forces into deflection. It permits to make use of high electrostatic forces generated in small gaps and thus gives access to large actuator deflections. We demonstrate that quasi-static deflections as large as four times the gap size are possible.